Initial Investigation of Nature‐Based, Child‐Centered Play Therapy: A Single‐Case Design. (October 2015) - Swank, Jacqueline M.; Shin, Sang Min; Cabrita, Carla; Cheung, Christopher; Rivers, Brittany
<x xml:space="preserve">Abstract</x> The authors implemented an A‐B‐A single‐case research design to examine the degree of treatment effect for a nature‐based, child‐centered play therapy intervention with early elementary school children (N = 4) exhibiting behavioral problems. Two participants exhibited behavioral change during the 7‐week intervention and maintained the change during follow‐up, as measured by classroom observations. Implications for using this approach in counseling are discussed.